Új tendenciák a légi utasok jogainak uniós szabályaiban - Angyal, Zoltán (Debreceni Jogi Műhely, 2013)
Regulation (EC) No 261/2004 depending on the circumstances of the travel disruption, requires air carriers to: provide passengers with assistance, such as meals, refreshments, telephone calls and hotel accommodation; offer re-routing and refunds; pay a flat-rate compensation of up to €600 per passenger, depending on the flight distance; and proactively inform passengers about their rights.Under the Montreal Convention (as translated by Regulation (EC) No 2027/97 into EU law), a passenger may be entitled to compensation in case of mishandled baggage (but with a limit of about €1200), except if the airline can demonstrate it has taken all reasonable measures to avoid the damages or it was impossible to take such measures. Airlines often fail to offer passengers the rights to which they are entitled in instances of denied boarding, long delays, cancellations or mishandled baggage, in particular under Regulation (EC) No 261/2004 ("the Regulation") and Regulation (EC) No 2027/97. Case law has had a decisive impact on the interpretation of the Regulation. The Commission Communication of 11 April 2011 reported on the varying interpretation being taken on the provisions of Regulation (EC) No 261/2004, due to grey zones and gaps in the current text, and the non-uniform enforcement across Member States. Furthermore, it is difficult for passengers to enforce their individual rights. With regard to Regulation (EC) No 261/2004, the European Parliament asks the Commission to propose a clarification of the passengers' rights, in particular the notion of ‘extraordinary circumstances’. On 13 March 2013, the European Commission made a proposal for a regulation of the European Parliament and of the Council amending Regulation (EC) No 261/2004 establishing8common rules on compensation and assistance to passengers in the event of denied boarding and of cancellation or long delay of flights and Regulation (EC) No 2027/97 on air carrier liability in respect of the carriage of passengers and their baggage by air. This paper takes a closer look at this proposal. The proposal aims to improve enforcement by clarifying key principles and implicit passenger rights that have given rise to many disputes between airlines and passengers in the past; and by enhancing and better coordinating the enforcement policies carried out on a national level. Issues covered by the proposal are the following.Definition of "extraordinary circumstances"Right to compensation in case of long delaysRight to reroutingRight to careMissed connecting flightRescheduling Tarmac delaysPartial ban of the "no show" policyRight to informationHandling of individual claims and complaintsBetter take into account the financial capacities of the air carriersEnsure better enforcement of passenger rights with regard to mishandled baggageAdapt liability limits in accordance to general price inflation